Prevalence of Hepatitis B Virus Infection and Circulating Genotypes among HIV/AIDS Patients Attending Hospitals in Nasarawa State, Nigeria (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Hepatitis B virus (HBV) prevalence remains high in sub-Saharan Africa, including Nigeria. We aimed to determine the seroprevalence of Hepatitis B Virus infection among HIV/AIDS patients attending some health care facilities in Nasarawa State, Nigeria. A total of 300 plasma of HIV/AIDS patients were randomly collected and screened for HBsAg using Rapid Test Kits. The overall prevalence of HBsAg in the selected hospitals among HIV/AIDS patients was 24 (8%) of which FMC Keffi, GH Nasarawa, GH Garaku had 7%, 6% and 11% respectively. The detection of HBsAg genotypes was carried out using Polymerase Chain Reaction technology (PCR). Of the 24 seropositive samples detected in the three hospitals, only 3 samples were detected molecularly to be positive which are all with genotype B. Of the 3 samples molecularly detected, 2 are from GHN and 1 from GHG.